Cost-effectiveness study of antidiabetic drugs in type 2 diabetes mellitus patients from Mumbai, India - Limaye, Dnyanesh; Todi, Krishna; Shroff, Jay; Ramaswamy, Ashutosh; Kulkarni, Priyanka; Limaye, Vaidehi; Fortwengel, Gerhard (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes is fast gaining the status of a potential epidemic in India, with >62 million individuals currently diagnosed with the disease. India currently faces an uncertain future in relation to the potential burden that diabetes may impose on the country. An estimated US 2.2 billion would be needed to sufficiently treat all cases of type 2 diabetes mellitus (T2DM) in India. Many interventions can reduce the burden of this disease. However, health care resources are limited; thus, interventions for diabetes treatment should be prioritized. The present study assesses the cost-effectiveness of antidiabetic drugs in patients with T2DM from Mumbai, India. Methods: A prospective cross-sectional study was performed to assess the cost-effectiveness of antidiabetic drugs in patients with T2DM. Face-to-face interviews were conducted by using a validated questionnaire in a total of 152 (76 males, 76 females) patients with T2DM from F-North Ward, Mumbai, India. Cost-effectiveness was determined on the basis of cost of antidiabetic drug/s, efficacy, adverse drug reactions, safety of administration, frequency of administration, and bioavailability. Results: For treatment of T2DM in non-obese participants, Glimepiride+Pioglitazone costed least (`3.7) per unit of effectiveness followed by Glimepiride (`6.6), Gliclazide (`8.1), Repaglinide (`24.5), and Vildagliptin (`45.2). For treatment of T2DM in obese participants, Metformin cost least (` 6.7) per unit of effectiveness followed by Glimepiride + Metformin (`5.9) and Repaglinide (`24.5). Conclusions: In case of non-obese participants, cost effectiveness and prescribed treatments did not show a match, while for obese participants prescribed treatments were in line with cost effectiveness.